Theses Originality: An Initial Effort to Examine Studentsâ Final Projects - Zulfikar, Teuku; Elismawati, Elismawati; Yuhardi, Yuhardi (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
Thesis is a prerequisite for graduation in all academic institutions. Higher Education institutions, such as Imam Bonjol Islamic State Institute requires its students to write a thesis in order to graduate. Students write their theses and they were examined before the board of examiners. However, students found it difficult to write âgoodâ theses that show academic honesty and high level of originality. This is a big issue in our institution, this article, therefore examines factors that reduce originality of studentsâ theses. Having analysed over 10 theses using content analysis method, the authors found that almost all theses contain issues that reduces the originality of the theses. Students frequently commit structural plagiarism, in which they tend to follow the structure of their colleaguesâ theses, and only made minor changes. Other finding showed that in stating their research problem, students make a claim without appropriate justification. Issues of referencing and paraphrasing are two important issues that reduce qualities of studentsâ theses.